PEMBERLAKUAN UMK (UPAH MINIMUM KABUPATEN/KOTA) TERHADAP KESEJAHTERAAN PEKERJA/BURUH - Agustine, Michele; Ariawan, I Gusti Ketut (Kertha Negara : Journal Ilmu Hukum, 2013)
Wages play an important role and it is typical that is a industrial relation. The government has participated in addressing the issue of wages through various policies as outlined in the legislation, one of which is the minimum wage. In a private company, has set minimum wages Regencies / Cities (UMK) has been established by the government for the workers / laborers. Therefore, this paper will describe the application of minimum wages Regencies / Cities on the welfare of workers / laborers.
Keywords: Industrial Relation, Workers/Laborers, Minimum Wages